Zero-waste IT solutions in Poland - Wyrobek, Joanna; Surowka, Marcin; Łach, Katarzyna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The article discusses various IT to avoid food waste solutions available in Poland, including mobile phone applications, websites, and discussion forums. The research thesis put forward in the paper says that Poles only use solutions that directly generate financial benefits. Other applications are little known or unknown, which shows that zero-waste solutions must take economic aspects into account. Saving food must pay off both for the person donating the food and for the person receiving or buying the food. The second aspect is undoubtedly the cost of access to a given solution, Poles knew almost only free applications.